Restrictions to Civil Liberties in a Pandemic and Satisfaction with Democracy - Daniel Graeber; Lorenz Meister; Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2023)
In times of crises, democracies face the challenge of balancing effective interventions with civil liberties. This study examines German states' response during the early stages of the COVID-19 pandemic, focusing on the interplay between civil liberties and public health goals. Using state-level variation in mobility restrictions, we employ a difference-in-differences design to show that stay-at-home orders notably increased satisfaction with democracy and shifted political support towards centrist parties. Stay-at-home orders increased satisfaction with democracy most among individuals who had been exposed to the authoritarian regime of the German Democratic Republic. A potential explanation is that these individuals had got used to more restrictive state interventions. Moreover, we find suggestive evidence that satisfaction with democracy increases more among individuals who are obese or have low vitality, possibly because their benefit from the mobility restrictions is higher. However, these differences are not statistically significant.
Keywords: D72; H12; I12; I18; P26; 330; perceptions of public policies; satisfaction with democracy; Covid-19